DISFLUENCY IN PRODUCING SPEECH ON THE CONTESTANTS OF STAND-UP COMEDY INDONESIA 7 AUDITION - Ariyoga, Majid (PEOPLE: International Journal of Social Sciences, 2018)
This paper focused on disfluency in producing speech (DPS), the imperfectness of a person in producing speech. The subjects of this study were the contestants of Stand-Up Comedy Indonesia Season 7 (SUCI 7) audition organized by Kompas TV in Jakarta. In that event, several contestants made DPS when they performed stand-up comedy, so their speech did not run well. Because that phenomenon associated with mental and language process in mind, it was exactly analyzed through Psycholinguistics study. This study had two research problems, namely 1) what were the kinds of DPS made by the contestants of the SUCI 7 audition; and 2) what were the factors causing the DPS on the contestants of the SUCI 7 audition. Based on such research problems, the purposes of this study were 1) systematically to explain the kinds of DPS made by these contestants; and 2) to reveal the main factors causing DPS on these contestants. In analyzing DPS, the author combined the theory of pause (filled and silent pause) by Dardjowidjojo (2014), and the theory of slip of the tongue by Carrol (2008). The results showed that five observed contestants of the SUCI 7 audition made DPS consisting of filled pause, silent pause, addition, substitution, and blend. The factor mostly causing the DPS on these contestants were nervousness, while the fewest one is hurry. Through this study, the readers were expected to understand DPS and to improve self-preparation for speech.